The effect of a radiation field on excitation and ionisation in non-LTE high energy density plasmas - Rose,SJ (2013)
We look at the direct effect of an ambient radiation field on excitation and ionisation in a non-LTE high energy density plasma. The equations that determine the excitation and ionisation are presented together with a comparison between theory and experiment for a number of cases. In particular we look at so-called photo-ionised plasmas which are also of interest in astrophysics.